European Journal of Mechanics - B/Fluids - European Journal of Mechanics - B/Fluids (Elsevier, 2026)
The European Journal of Mechanics - B/Fluids publishes papers in Eglish in all fields of fluid mechanics. Although investigations in well-established areas are within the scope of the journal, recent developments and innovative ideas are particularly welcome. Theoretical, computational and experimental papers are equally welcome. Mathematical methods, be they deterministic or stochastic, analytical or numerical, will be accepted provided they serve to clarify some identifiable problems in fluid mechanics, and provided the significance of results is explained. Similarly, experimental papers must add physical insight in to the understanding of fluid mechanics.
FI 0.89
Q2
Keywords: Physical Sciences & Engineering; Fluid Dynamics; Dinámica de fluidos; Acuerdos transformativos; Transformative agreements; Mecánica de fluidos; Métodos matemáticos